Composite Electrolytes

JP7599784B2Active Publication Date: 2024-12-16KK TOYOTA CHUO KENKYUSHO +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021026945
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-24
Publication Date
2024-12-16
Estimated Expiration
2041-02-24

AI Technical Summary

Technical Problem

Existing solid polymer electrolytes in MEAs are prone to deterioration due to radical attack, leading to increased resistance, cross leakage, and reduced lifespan, with conventional inhibitors causing conductivity loss and uneven distribution issues.

Method used

A composite electrolyte containing tungsten oxide and specific metal compounds or ions, within a controlled ratio, dispersed in the solid polymer electrolyte to decompose hydrogen peroxide and scavenge radicals, maintaining high durability with minimal conductivity loss.

Benefits of technology

The composite electrolyte effectively suppresses electrolyte deterioration by simultaneously decomposing hydrogen peroxide and scavenging radicals, achieving high durability with small additive amounts, thereby maintaining conductivity and preventing cracking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007599784000002
    Figure 0007599784000002
  • Figure 0007599784000003
    Figure 0007599784000003
  • Figure 0007599784000001
    Figure 0007599784000001
Patent Text Reader

Abstract

To provide a composite electrolyte which has a relatively low content of a degradation inhibitor and exhibits high deterioration suppressing effect.SOLUTION: There is provided a composite electrolyte which comprises a solid polymer electrolyte, tungsten oxide dispersed in the solid polymer electrolyte, a compound containing a metal element dispersed in the solid polymer electrolyte and / or an ion of the metal element which is ion-exchanged with a proton of an acid group contained in the solid polymer electrolyte. The composite electrolyte satisfies the following expressions: 0.0001≤W / A<0.25 and 0.0005≤M / A≤0.15. Provided that W / A is a ratio of molar numbers (W) of tungsten contained in the tungsten oxide to the molar numbers (A) of the acid group and M / A is a ratio of molar numbers (M) of the metal element to the molar numbers (A) of the acid group.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite electrolyte, and more specifically to a composite electrolyte containing an additive that has an effect of suppressing the generation of radicals that cause deterioration of a solid polymer electrolyte and / or an effect of scavenging radicals. [Background technology]

[0002] Membrane electrode assemblies (MEAs) are used in the areas where electrochemical reactions occur in soda electrolysis devices, water electrolysis devices, fuel cells, etc. It is said that MEAs are deteriorated when the electrolyte is attacked by radicals generated directly by the direct reaction of oxygen and hydrogen, or by electrochemical reactions, or by radicals generated via hydrogen peroxide. For example, in fuel cells, radical attack is known to increase the resistance of the electrolyte membrane, increase cross leakage, and shorten the lifespan due to thinning. Furthermore, degradation products generated by radical attack may cause catalyst poisoning, which may result in a decrease in electrolytic performance and cell performance.

[0003] In order to solve this problem, various proposals have been made in the past. For example, Patent Document 1 states: (a) A catalyst ink containing 0.25 times the molar amount of H2WO4 and 0.05 times the molar amount of Ce(NO3)3 relative to the molar amount of sulfonic acid groups in Nafion (registered trademark), or (b) Catalyst ink containing 0.25 times the molar amount of H2WO4 and 0.05 times the molar amount of Mn(NO3)3 relative to the molar number of sulfonic acid groups in Nafion (registered trademark) MEAs fabricated using the method are disclosed. The document states that an MEA made using a catalyst ink containing degradation inhibitors (H2WO4, Ce(NO3)3, Mn(NO3)3) has a higher molecular weight retention rate of the solid polymer electrolyte than an MEA made using a catalyst ink that does not contain degradation inhibitors.

[0004] Patent Document 2 discloses a polymer electrolyte membrane containing a perfluorosulfonic acid resin and zirconia having a primary particle diameter of 10 nm, in which the ratio of the mass (A) of the perfluorosulfonic acid resin to the mass (B) of the zirconia (=A / B ratio) is 99 / 1. The same document states: (A) In the case where zirconia, which catalytically decomposes hydrogen peroxide, is added to a perfluorosulfonic acid resin, adjusting the primary particle size of the zirconia to 1 nm to 50 nm increases the specific surface area of ​​the zirconia, and the number of hydrogen peroxide decomposition reaction sites increases dramatically; and (B) This suppresses the deterioration of the polymer electrolyte membrane. is stated.

[0005] Furthermore, Patent Document 3 states: (a) An electrolyte membrane made of Nafion (registered trademark) is immersed in a 0.1 M aqueous solution of sodium tungstate at 90° C. for 30 minutes. (b) The electrolyte membrane is then removed from the aqueous solution and washed with water; (c) The electrolyte membrane is then immersed in 0.5 M sulfuric acid at 90° C. for 30 minutes. The present invention discloses a transition metal oxide-containing solid polymer electrolyte membrane obtained by the above process. The same document states: (A) By such a method, a transition metal oxide-containing solid polymer electrolyte membrane containing 2 wt % tungsten oxide hydrate can be obtained; and (B) The electrolyte membrane containing tungsten oxide hydrate has a lower fluorine dissolution rate than the electrolyte membrane not containing tungsten oxide hydrate. is stated.

[0006] As described in Patent Documents 1 to 3, the durability of a solid polymer electrolyte is improved by adding a certain type of deterioration inhibitor to the solid polymer electrolyte. In general, it is considered that the durability of a solid polymer electrolyte is improved as the amount of deterioration inhibitor added increases. However, when a degradation inhibitor is added to a solid polymer electrolyte, the conductivity decreases as the amount of degradation inhibitor increases because the particles of the degradation inhibitor physically inhibit the proton conduction of the electrolyte. In addition, if the amount of degradation inhibitor added is excessive, the degradation inhibitor will be distributed unevenly in the electrolyte membrane or catalyst layer due to precipitation or aggregation of the degradation inhibitor, and the membrane or catalyst layer may crack or peel off during the preparation of the electrolyte membrane or MEA. On the other hand, if the amount of degradation inhibitor is reduced to avoid these problems, durability often becomes insufficient. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 5194448 [Patent Document 2] Patent No. 5354935 [Patent Document 3] Patent No. 4326271 Summary of the Invention [Problem to be solved by the invention]

[0008] An object of the present invention is to provide a composite electrolyte that has a relatively small content of a degradation inhibitor and exhibits a high degradation inhibitor effect. [Means for solving the problem]

[0009] In order to solve the above problems, the composite electrolyte according to the present invention has the following configuration. (1) The composite electrolyte is A solid polymer electrolyte; tungsten oxide dispersed in the solid polymer electrolyte; a compound containing a metal element dispersed in the solid polymer electrolyte and / or an ion of the metal element which is ion-exchanged with a proton of an acid group contained in the solid polymer electrolyte; It is equipped with: (2) The composite electrolyte satisfies the relationships of the following formulas (1) and (2). 0.0001≦W / A<0.25 …(1) 0.0005≦M / A≦0.15 …(2) however, W / A is the ratio of the number of moles of tungsten (W) contained in the tungsten oxide to the number of moles of the acid group (A); M / A is the ratio of the number of moles of the metal element (M) to the number of moles of the acid group (A). Effect of the Invention

[0010] When tungsten oxide and a certain type of metal compound and / or metal ion are added to a solid polymer electrolyte at the same time, high durability can be obtained even if the amount of these added is relatively small. (a) Tungsten oxide has the effect of decomposing hydrogen peroxide and rendering it harmless. Even if the amount added is small, it has a high hydrogen peroxide decomposition effect. (b) Certain metal compounds and metal ions have the ability to scavenge radicals. (c) When tungsten oxide coexists with a certain metal compound and / or metal ion, the hydrogen peroxide decomposition effect of tungsten oxide is improved, and (d) Even if radicals are generated from hydrogen peroxide that is not decomposed by tungsten oxide, the metal compound and / or metal ion effectively scavenges the radicals. It is thought that. [Brief description of the drawings]

[0011] [Figure 1] Fig. 1(A) is a diagram showing the relationship between the W / A ratio and the fluoride ion ejection rate (FER) of an electrolyte membrane (M / A=0.015) containing WO3 or WO3+Ce. Fig. 1(B) is a diagram showing the relationship between the W / A ratio and the fluoride ion ejection rate (FER) of an electrolyte membrane (M / A=0.015) containing WO2 or WO2+Ce. [Diagram 2]FIG. 1 is a graph showing the relationship between the M / A ratio and the fluoride ion expulsion rate (FER), and the relationship between the M / A ratio and the conductivity decrease rate when W / A=0.0043. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] An embodiment of the present invention will be described in detail below. [1. Composite electrolytes] The composite electrolyte according to the present invention comprises: A solid polymer electrolyte; tungsten oxide dispersed in the solid polymer electrolyte; a compound containing a metal element dispersed in the solid polymer electrolyte and / or an ion of the metal element which is ion-exchanged with a proton of an acid group contained in the solid polymer electrolyte; It is equipped with:

[0013] [1.1. Solid polymer electrolyte] In the present invention, the material of the solid polymer electrolyte is not particularly limited. The solid polymer electrolyte may be either a fluorine-based electrolyte or a hydrocarbon-based electrolyte. The composite electrolyte may contain one of these solid polymer electrolytes, or may contain two or more of them. The type of acid group in the solid polymer electrolyte is not particularly limited. Examples of the acid group include a sulfonic acid group, a carboxylic acid group, a phosphonic acid group, and a sulfonimide group. The solid polymer electrolyte may contain only one of these acid groups, or may contain two or more of them.

[0014] Examples of fluorine-based electrolytes include Nafion (registered trademark), Flemion (registered trademark), Aquivion (registered trademark), and Aciplex (registered trademark). The fluorine-based electrolyte includes not only fully fluorinated electrolytes that do not contain C—H bonds in the polymer structure, but also partially fluorinated electrolytes that contain C—H bonds and C—F bonds in the polymer structure.

[0015] Examples of hydrocarbon-based electrolytes include (a) wholly aromatic hydrocarbon-based electrolytes composed of polyetheretherketone, polysulfone, polyethersulfone, polyimide, polyphenylene, polyamide, polyamideimide, or derivatives thereof, into which acid groups such as sulfonic acid groups are introduced, (b) partially aromatic hydrocarbon-based electrolytes having an aromatic ring in a part of the polymer chain of aliphatic hydrocarbon-based electrolytes, and the like.

[0016] [1.2. Tungsten Oxide] Tungsten oxide is dispersed in the solid polymer electrolyte. "Dispersion" means (a) a state in which the surroundings of primary particles or higher-order particles such as secondary particles of tungsten oxide are surrounded by a solid polymer electrolyte, or (b) a state in which a solid polymer electrolyte exists in a part of the surroundings of primary particles or higher-order particles such as secondary particles of tungsten oxide is meant. Tungsten oxide mainly has the effect of decomposing hydrogen peroxide into harmless substances. Therefore, when an appropriate amount of tungsten oxide is added to the solid polymer electrolyte, deterioration of the solid polymer electrolyte can be suppressed.

[0017] In the present invention, the type of tungsten oxide is not particularly limited. Examples of tungsten oxide include (a) various oxides represented by WO3, WO2, WO 2.5 and the like, where WO x (2 ≦ x ≦ 3, x includes non-integers), (b) hydrates of WO x (WO x ·nH2O) (2 ≦ x ≦ 3, 0 < n < 3, x and n each include non-integers), and the like. The composite electrolyte may contain any one of these tungsten oxides, or may contain two or more thereof. Tungsten oxide is particularly WO3, WO2, and WO 2.5It is preferable to use at least one selected from the group consisting of the following, since all of these are stable under acidic conditions.

[0018] [1.3. Compounds and / or ions containing metal elements] Compounds and ions containing certain metal elements mainly have the effect of scavenging radicals, and therefore, by adding an appropriate amount of a compound and / or ion containing a metal element to a solid polymer electrolyte, deterioration of the solid polymer electrolyte can be suppressed.

[0019] Examples of metal elements include Ce, Ag, Cs, Sn, Mn, Ti, Co, Ni, Zn, Zr, Ru, Rh, Pd, Pt, Pr, etc. The composite electrolyte may contain any one of these metal elements, or may contain two or more of them. The metal element is preferably at least one element selected from the group consisting of Ce, Ag, Cs, Sn, and Mn, since these elements all have a strong effect of suppressing the generation of radicals or scavenging radicals.

[0020] The metal compound may be a water-soluble compound or a poorly soluble compound. When a water-soluble metal compound is used, the metal compound dissociates in the composite electrolyte, and some of the protons of the acid groups of the solid polymer electrolyte are replaced with metal ions. On the other hand, when a poorly soluble metal compound is used, the metal compound is dispersed in the solid polymer electrolyte. Examples of metal compounds include nitrates, sulfates, carbonates, formates, acetates, citrates, perchlorates, phosphates, chlorides, fluorides, hydroxides, and acetylacetonate compounds.

[0021] [1.4. Composition] The composite electrolyte according to the present invention satisfies the relationships of the following formulas (1) and (2). 0.0001≦W / A<0.25 …(1) 0.0005≦M / A≦0.15 …(2) however, W / A is the ratio of the number of moles of tungsten (W) contained in the tungsten oxide to the number of moles of acid groups (A) contained in the solid polymer electrolyte; M / A is the ratio of the number of moles of the metal element (M) to the number of moles of the acid group (A) contained in the solid polymer electrolyte.

[0022] [1.4.1. Formula (1)] Formula (1) represents the range of the W / A ratio. If the W / A ratio is too small, the effect of suppressing the degradation of the solid polymer electrolyte is reduced. Therefore, the W / A ratio must be 0.0001 or more. The W / A ratio is preferably 0.0002 or more, and more preferably 0.0004 or more.

[0023] On the other hand, if the W / A ratio is too large, the conductivity of the solid polymer electrolyte may decrease, or the tungsten oxide may aggregate and the membrane may crack. Therefore, the W / A ratio must be less than 0.25. The W / A ratio is preferably 0.10 or less, and more preferably 0.05 or less.

[0024] It is particularly preferable that the composite electrolyte satisfies the relationship of the following formula (1'). 0.0002≦W / A≦0.10 …(1')

[0025] [1.4.2. Formula (2)] Even when only tungsten oxide is added to the solid polymer electrolyte, the deterioration of the solid polymer electrolyte can be effectively suppressed. However, when a certain metal compound and / or metal ion is further added in addition to tungsten oxide, the deterioration of the solid polymer electrolyte is further suppressed due to the synergistic effect of these. In order to obtain such an effect, the M / A ratio needs to be 0.0005 or more. The M / A ratio is preferably 0.001 or more, more preferably 0.005 or more.

[0026] On the other hand, if the M / A ratio is too large, the conductivity of the solid polymer electrolyte may decrease. Therefore, the M / A ratio must be 0.15 or less. The M / A ratio is preferably 0.10 or less, more preferably 0.05 or less, more preferably 0.04 or less, and even more preferably 0.03 or less.

[0027] It is particularly preferable that the composite electrolyte satisfies the relationship of the following formula (2'). 0.001≦M / A≦0.10 …(2')

[0028] [2. Manufacturing method of composite electrolyte] The composite electrolyte according to the present invention comprises: (a) preparing a solution (A) in which a solid polymer electrolyte is dissolved or dispersed in a solvent; (b) further dissolving or dispersing tungsten oxide and a metal compound in the solution (A) to obtain a solution (B); (c) Removing the solvent from solution (B) It can be produced by the above method.

[0029] In addition, various members containing the composite electrolyte according to the present invention can be produced by various methods. For example, an electrolyte membrane made of the composite electrolyte can be produced by casting the solution (B) on a suitable substrate surface and removing the solvent. Alternatively, the electrolyte membrane may be immersed in an aqueous solution of a tungstate to introduce the tungstate into the electrolyte membrane, and then the electrolyte membrane may be treated with an acid to fix the tungsten oxide in the electrolyte membrane. Also, the electrolyte membrane may be immersed in a solution of a tungsten alkoxide to introduce the tungsten alkoxide into the electrolyte membrane, and the tungsten alkoxide may be condensed in the electrolyte membrane.

[0030] Furthermore, when an electrolyte membrane is produced using the composite electrolyte of the present invention, the electrolyte membrane may be composed of only the composite electrolyte of the present invention, or may be a composite of the composite electrolyte and a reinforcing material. In this case, the type of the reinforcing material is not particularly limited. Examples of reinforcing materials include: (a) Porous membranes and nonwoven fabrics of fluororesins such as polytetrafluoroethylene (PTFE), perfluoroalkoxyalkane (PFA), perfluoroethylenepropene copolymer (FEP), and ethylenetetrafluoroethylene copolymer (ETFE); (b) Porous membranes and nonwoven fabrics of hydrocarbon resins such as polyethylene (PE) and polypropylene (PP), etc.

[0031] A catalyst layer containing a composite electrolyte can be produced by further dispersing an electrode catalyst in solution (B) to obtain solution (C), casting solution (C) on a suitable substrate surface, and removing the solvent. Alternatively, the catalyst layer may be formed by applying or spraying the solution (C) onto the surface of the electrolyte membrane and then removing the solvent.

[0032] [3. Effect] Tungsten oxide and compounds or ions containing certain metal elements both have the effect of suppressing degradation of solid polymer electrolytes. However, when these are added alone to a solid polymer electrolyte, there is a limit to the effect of improving durability. In addition, in order to obtain a relatively high durability, it is necessary to add a relatively large amount of these additives.

[0033] In contrast, when tungsten oxide and a certain type of metal compound and / or metal ion are added to the solid polymer electrolyte at the same time, high durability can be obtained even if the amount of these added is relatively small. (a) Tungsten oxide has the effect of decomposing hydrogen peroxide and rendering it harmless. Even if the amount added is small, it has a high hydrogen peroxide decomposition effect. (b) Certain metal compounds and metal ions have the ability to scavenge radicals. (c) When tungsten oxide coexists with a certain metal compound and / or metal ion, the hydrogen peroxide decomposition effect of tungsten oxide is improved, and (d) Even if radicals are generated from hydrogen peroxide that is not decomposed by tungsten oxide, the metal compound and / or metal ion effectively scavenges the radicals. It is thought that. EXAMPLES

[0034] (Examples 1 to 14, Comparative Examples 1 to 3) [1. Sample preparation] [1.1. Examples 1 to 13] 1-propanol, ultrapure water, metal salt aqueous solution, and FeSO4 aqueous solution (radical generator for dry Fenton test) were added to and mixed with an electrolyte solution (D2020, Nafion (registered trademark) dispersion solution, 1000EW, 20wt%, manufactured by Chemours Co., Ltd.) to obtain a first solution. The blending ratio (mass ratio) of the electrolyte solution, 1-propanol, and water (total amount of water contained in the ultrapure water, metal salt aqueous solution, and FeSO4 aqueous solution) was electrolyte solution: 1-propanol: water = 10: 7: 3.

[0035] The metal salts used were Ce(NO3)3, AgNO3, CsNO3, SnSO4, or Mn(NO3)2. The amount of the metal salt aqueous solution was adjusted so that the M / A ratio was 0.015 or 0.029. The amount of the FeSO4 aqueous solution was adjusted so that the Fe in the electrolyte acid group was 0.015 or 0.029. 2+ The amount was set so that the substitution rate with ions was 1%.

[0036] Next, tungsten oxide was added to the first solution and dispersed by irradiating ultrasonic waves for 10 minutes to obtain a casting solution. WO3 or WO2 was used as the tungsten oxide. The amount of tungsten oxide was set to a W / A ratio of 0.0043, 0.0047, 0.043, or 0.047.

[0037] Cast solution: 1.50 g was collected in a φ35 mm flat petri dish and left to dry in a constant temperature room atmosphere (25 ° C) for several days to obtain a cast membrane. The cast membrane was then annealed (140 ° C, 15 minutes). The cast membrane was then taken out and rinsed with ultrapure water, and the cast membrane was sandwiched between filter paper and air-dried.

[0038] 1.2. Example 14 An electrolyte membrane (NR211, manufactured by Chemours Inc.) was heated and vacuum dried (80° C., 2 hours), and the dry weight of the electrolyte membrane was measured in a glove box. Next, in a glove box, W(OEt)5 (manufactured by Azumax Corporation) was added to dehydrated ethanol to prepare a 0.01 mass% tungsten compound solution. The dried electrolyte membrane was immersed in this tungsten compound solution. The amount of the tungsten compound solution was set to a W / A ratio of 0.0045. After immersion, the electrolyte membrane was taken out and air-dried.

[0039] Next, the electrolyte membrane was heated and vacuum dried (130°C, 2 hours) to condense W(OEt)5, resulting in the formation of WO 2.5 After heating and vacuum drying, the electrolyte membrane was immersed in ethanol for washing and air-dried. The electrolyte membrane was further heated and vacuum-dried (80°C, 2 hours) and then cooled to 50°C in a glove box. 2.5 The dry weight of the electrolyte membrane containing the above was measured.

[0040] Next, the obtained electrolyte membrane was immersed in a Ce(NO3)3 aqueous solution, and Ce ions were added to the electrolyte membrane. The amount of Ce added was set to a Ce / SO3H ratio of 0.015. Next, the electrolyte membrane was immersed in a FeSO4 aqueous solution, and Fe ions were added to the electrolyte membrane as a radical generator for the dry Fenton test. The amount of Fe added was set to 0.015. 2+ The amount was set so that the replacement rate with ions was 1%. After immersion, the electrolyte membrane was rinsed with ultrapure water, sandwiched between filter paper and air-dried. Furthermore, the electrolyte membrane was heated and vacuum-dried (80°C, 2 hours), and the dry weight of the electrolyte membrane was measured in a glove box.

[0041] [1.3. Comparative Examples 1 to 6] An electrolyte membrane was prepared in the same manner as in Example 1, except that Ce ions and WO3 were not added (Comparative Example 1). An electrolyte membrane was prepared in the same manner as in Example 1, except that WO3 was not added (Comparative Example 2). In this case, the amount of Ce ions added was set to an amount such that the Ce / SO3H ratio was 0.015. Furthermore, an electrolyte membrane was prepared in the same manner as in Example 1 except that no Ce ions were added (Comparative Example 3). Also, an electrolyte membrane was prepared in the same manner as in Example 2 except that no Ce ions were added (Comparative Example 4). An electrolyte membrane was prepared in the same manner as in Comparative Example 3 except that the amount of WO3 added, W / A, was set to 0.43 (Comparative Example 5). Furthermore, an electrolyte membrane was prepared in the same manner as in Comparative Example 4 except that the amount of WO2 added, W / A, was set to 0.23 (Comparative Example 6).

[0042] 2. Test Method [2.1. Dry Fenton test] The electrolyte membrane was vacuum dried (80°C, 2 hours) and subjected to a hydrogen peroxide vapor exposure test (dry Fenton test). A 3 mass% solution of hydrogen peroxide was dropped into a polytetrafluoroethylene (PTFE) evaporator heated to 170°C at a rate of 0.12 mL / min, and the entire amount was vaporized. N2 was added at 0.3 L / min to dilute the solution. After heating and vacuum drying, the electrolyte membrane, whose dry weight had been measured, was fixed to a PTFE net and placed in a PTFE inner tube heated to 95°C. Hydrogen peroxide vapor diluted with N2 was introduced and exposed for 5 hours. Under these conditions, the relative humidity at 95°C was calculated to be approximately 38%.

[0043] The hydrogen peroxide vapor that passed through the sample was collected by bubbling it into 100 mL of ultrapure water contained in a PE (polyethylene) container (surrounded by ice cooling). - The amount of F per unit time and unit mass of electrolyte was calculated from the mass of electrolyte and the test time using a fluorine composite electrode manufactured by Thermo Fisher Scientific. - The excretion rate (FER) (μg / mg / hr) was calculated.

[0044] [2.2. Conductivity decrease rate] The resistance of the electrolyte membrane was measured and the conductivity reduction rate was calculated according to the following procedure. That is, the electrolyte membrane was set in a two-terminal cell, and the resistance was measured by an AC impedance method. Furthermore, the membrane thickness and membrane width of the electrolyte membrane were obtained, and the conductivity of the electrolyte membrane was calculated. The measurement temperature was 25°C, and the relative humidity was RH20%. The ratio of the conductivity reduction amount when the metal element M was added to the conductivity of the membrane without the metal element M was taken as the conductivity reduction rate.

[0045] [3. Results] [3.1. Dry Fenton test] The results are shown in Table 1. Table 1 also shows the composition of each sample. Figure 1(A) shows the relationship between the W / A ratio and the fluoride ion ejection rate (FER) of an electrolyte membrane (M / A=0.015) containing WO3 or WO3+Ce. Figure 1(B) shows the relationship between the W / A ratio and the fluoride ion ejection rate (FER) of an electrolyte membrane (M / A=0.015) containing WO2 or WO2+Ce. The following can be seen from Table 1 and Figure 1.

[0046] (1) When the W / A ratio exceeded 0.1, the FER increased regardless of the type of tungsten oxide. (2) In the case of the electrolyte membrane containing only WO3 (Comparative Example 3), the FER was 0.079 μg / mg / hr, whereas in the case of the electrolyte membrane containing WO3 and Ce (Example 1), the FER was 0.034 μg / mg / hr. (3) In the case of the electrolyte membrane containing only WO2 (Comparative Example 4), the FER was 0.026 μg / mg / hr, whereas in the case of the electrolyte membrane containing WO2 and Ce (Example 2), the FER was 0.007 μg / mg / hr.

[0047] (4) Tungsten oxide is WO 2.5 The same was true when the metal element M was Ag, Cs, Sn, or Mn, and the FER was significantly reduced by adding an extremely small amount of tungsten oxide compared to when only tungsten oxide was added (Comparative Example 3) or when only Ce was added (Comparative Example 2).

[0048] [Table 1]

[0049] [3.2. Conductivity decrease rate] Figure 2 shows the relationship between the M / A ratio and the fluoride ion expulsion rate (FER) when W / A=0.0043, and the relationship between the M / A ratio and the conductivity decrease rate. Note that the region where M / A>0.029 in Figure 2 shows the simulation results. The following can be seen from Figure 2. (1) The FER decreased as the M / A ratio increased. However, the rate of decrease in conductivity increased as the M / A ratio increased. This is because the proportion of protons in the acid groups in the electrolyte that are replaced by ions of the metal element M increases as the M / A ratio increases. (2) To achieve both a low FER and a low conductivity decline, the M / A ratio must be 0.15 or less. Furthermore, the conductivity decline can be minimized by keeping the M / A ratio at 0.10 or less.

[0050] Although the embodiment of the present invention has been described in detail above, the present invention is not limited to the above embodiment, and various modifications are possible without departing from the gist of the present invention. [Industrial Applicability]

[0051] The composite electrolyte according to the present invention can be used as an electrolyte membrane for a polymer electrolyte fuel cell or a polymer electrolyte water electrolysis device, a catalyst layer ionomer, or the like.

Claims

1. A composite electrolyte comprising: (1) The composite electrolyte is A solid polymer electrolyte; tungsten oxide dispersed in the solid polymer electrolyte; a compound containing a metal element dispersed in the solid polymer electrolyte and / or an ion of the metal element ion-exchanged with a proton of an acid group contained in the solid polymer electrolyte; It is equipped with: (2) The composite electrolyte satisfies the relationships of the following formulas (1) and (2). 0.0001≦W / A<0.25…(1) 0.0005≦M / A≦0.15 ... (2) however, W / A is the ratio of the number of moles of tungsten (W) contained in the tungsten oxide to the number of moles of the acid group (A); M / A is the ratio of the number of moles of the metal element (M) to the number of moles of the acid group (A). (3) The metal element includes at least one element selected from the group consisting of Ce, Ag, Cs, Sn, and Mn.

2. The composite electrolyte according to claim 1 , which satisfies the following formula (1′): 0.0002≦W / A≦0.10 ... (1')

3. The composite electrolyte according to claim 1 or 2, which satisfies the following formula (2'): 0.001≦M / A≦0.10 ... (2')

4. The tungsten oxide is WO x , and W.O. x ・nH 2 4. The composite electrolyte according to claim 1 , comprising at least one selected from the group consisting of: x, n, 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100, 101, 102, 103, 104, 105, 106, 107, 108, 109, 109, 108, 109, 110, 111, 112, 113, 114, 11

5. The tungsten oxide is WO 3 , W.O. 2 , and W.O. 2.5 5. The composite electrolyte according to claim 1, further comprising one or more oxides selected from the group consisting of:

Citation Information

Patent Citations

  • Yosetsuyokaabudochitsupu

    JP1976094448A

  • Information converting device

    JP1978054935A

  • Transition metal oxide containing solid polyelectrolyte

    JP2005019232A

  • Electrolyte membrane electrode assembly for solid polymer fuel cell and the solid polymer fuel cell

    JP2005093234A

  • Solid polyelectrolyte, as well as solid polymer fuel cell, and its manufacturing method

    JP2006338912A